Template synthesis of mesoporous nanofilms and nanowires and their applications - Xue, Tong (2013)
Template-based growth is an inexpensive and practicable methodology which could produce various types of materials and controllable structure such as pore size, wire length and packing density. In the candidates of templates family, porous anodic alumina (PAA) templates as hard templates are most famous to be used in fabricating ordered nanowire and nanotube arrays, and while the lyotropic liquid crystalline (LLC) phases of surfactant as soft templates are versatile to use in synthesizing mesoporous films. In this thesis, we focus on the template synthesis of ordered mesoporous nanofilms and nanwires, and their applications in semiconductors, supercapacitors and electrochemical catalysts. In our study, mesoporous dual layers of polyaniline (PANI) supported Cu2O and Se0.5Te0.5 films have been designed and synthesized by using LLC template for the first time. Mesoporous Co(OH)2 nanowires and Pt on mesoporous carbon nanowires (Pt/MCNWs) have been fabricated via PAA and LLC combined dual templates with enhanced electrochemical behavior.